Pay and Job Rank Amongst Academic Economists in the UK: Is Gender Relevant? - Karen A. Mumford; Cristina Sechel (Institute of Labor Economics (IZA), 2019)
This article presents and explores a rich new data source to analyse the determinants of pay and job rank amongst academic Economists in the UK. Characteristics associated with individual productivity and workplace features are found to be important determinants of the relative wage and promotion structure in this sector. However, there is also a substantial unexplained gender pay gap. Men are considerably more likely to work in higher paid job ranks where there are also substantial within-rank gender pay gaps. We show that the nature of the gender pay gap has changed over the last two decades; but its size has not, suggesting a role for suitable policy intervention.
Keywords: A1; A11; A2; I3; J01; J31; J7; 330; economist; academia; pay-gap; gender